Le vote blanc et nul en Wallonie : analyse écologique et individuelle - Geoffrey Pion (Belgeo)
Blank and null votes are probably the electoral behaviour least taken into account by electoral studies. Though, in a democracy like Belgium, these votes are far from negligible and offer an untypical geography which underlines border areas. This paper will analyze this unknown electoral behaviour in an ecological and individual way. We will first build a multiple regression model in order to try to debrief the spatial variation of blank and null votes in Wallonia thanks to demographic and socioeconomic variables. Secondly, we will study the information retained by more than 2000 spoiled ballot papers. The study will highlight the opposition between rural and urban blank and null votes. The first ones are numerous, notably along the national borders, and reflect essentially hidden abstention or lack of interest in Belgian political life by citizens turned, in their private or professional life, towards France or Luxembourg. The second combine rejection of politics and ignorance of electoral rules in popular classes and first time voters.